Unfinished business : the negotiation of the CTBT and the end of nuclear testing - Johnson, Rebecca (New York ; Geneva : United Nations, 2009)
The Comprehensive Nuclear-Test-Ban Treaty (CTBT) remains a key piece of unfinished business of the nuclear age. As a growing number of governments and decision makers put forward ideas to move the world toward abolishing nuclear weapons, much can be learnt from how the CTBT was fought for, opposed and finally negotiated between 1994 and 1996. The treaty's necessity was underlined when the Democratic People's Republic of Korea conducted a nuclear test explosion in 2006, but more than a decade of political and institutional obstacles have prevented the CTBT from entering into full legal effect. New opportunities exist today for CTBT entry into force. Understanding the story of the treaty will enable civil society, governments and diplomats to assist in this process and to develop more effective strategies and tools to bring about future disarmament agreements. --
Introduction -- Cold war attempts to ban nuclear explosions -- Putting the test ban back on the table -- The struggle for a zero-yield test ban -- Making the treaty ban civilian as well as military nuclear explosions -- Entry into force and the endgame -- Designing a robust verification regime -- Lessons for future multilateral security negotiations -- Securitng the CTBT.
"UNIDIR, United Nations Institute for Disarmament Research." ; "UNIDIR/2009/2." --Portada.
"United Nations Publications Sales No. GV. E.09.0.4"--Contraportada.
Keywords: TRATADO DE PROHIBICION COMPLETA DE LOS ENSAYOS NUCLEARES; NO PROLIFERACION NUCLEAR; CONTROL DE ARMAS NUCLEARES -- COOPERACION INTERNACIONAL; ARMAS NUCLEARES -- PRUEBAS